Excitation functions and thick target yields of (α,xn) and (α,αxn) reactions on 103Rh - Ozafran, M. J.; Vazquez, M. E.; Vega Vedoya, M. de la; Nassiff, S. J. (1980)
Fil: Ozafran, M. J. Comisión Nacional de Energía Atómica; Argentina